2022
DOI: 10.1056/nejmoa2115961
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Tricuspid Repair in Patients with Degenerative Mitral Regurgitation

Abstract: Background: Tricuspid regurgitation is common in patients with severe degenerative mitral regurgitation. However, the evidence base is insufficient to inform a decision about whether to perform tricuspid-valve repair during mitral-valve surgery in patients who have moderate tricuspid regurgitation or less-than-moderate regurgitation with annular dilatation. Methods: We randomly assigned 401 patients who were undergoing mitral-valve surgery for degenerative mitral regurgitation to receive a procedure with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(106 citation statements)
references
References 38 publications
2
102
1
1
Order By: Relevance
“…According to the current guidelines, TA should be performed during concomitant left-sided valve surgery in patients with TR or dilated tricuspid annulus (6,7). Recent research further showed that the inclusion of TA at the time of mitral valve surgery resulted in a lower risk of a primary-end-point event at 2 years than those who underwent mitral-valve surgery alone (25). Nonetheless the severity of TR, in particular massive TR, is not one of the indications for surgical correction.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current guidelines, TA should be performed during concomitant left-sided valve surgery in patients with TR or dilated tricuspid annulus (6,7). Recent research further showed that the inclusion of TA at the time of mitral valve surgery resulted in a lower risk of a primary-end-point event at 2 years than those who underwent mitral-valve surgery alone (25). Nonetheless the severity of TR, in particular massive TR, is not one of the indications for surgical correction.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of major adverse events and the overall survival were similar in the groups with and without TV annuloplasty. 23 The present study is a retrospective cohort study from a single tertiary center with limitations inherent to its design. Due to the strict inclusion criteria, the sample size was relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study by Farooq and colleagues on TA plus mitral valve replacement there was no progression of TR reported at three years (11). Recently reported randomized controlled trial by Gammie and colleagues showed much lesser progression of moderate TR at two years (0.6% vs. 6.1% control group, relative risk, 0.09; 95% CI, 0.01 to 0.69) (3). Bernal and colleagues reported progression of TR during their 15,8 years mean follow up in 23,5% of the RHD population caused by recurrent rheumatic disease (12).…”
mentioning
confidence: 83%
“…It is reported that 65-85% of the population present with trivial to moderate TR which remain asymptomatic until it is discovered in an echocardiogram for preoperative cardiac evaluation or routine cardiovascular checkup (3). Moderate to severe TR occurs in patients with rightand left-sided congenital and acquired diseases and may be associated to bi-ventricular failure, increased risk for associated morbidity such as pulmonary arterial hypertension (PAH), hepatorenal syndrome and mortality (1,4,(7)(8)(9).…”
mentioning
confidence: 99%